Research on concentrated frequency-dependent parameter model for short overhead transmission lines based on first-order rational function fitting - Li, Botong; Sun, Mingyang; Wen, Weijie; Ji, Xiaotong; Xiao, Fan (Frontiers in Energy Research, 2023)
The impedance of power lines is influenced by geological conditions and skin effect, resulting in frequency-dependent characteristics. In this study, a centralized parameter frequency-dependent line model based on first-order rational function fitting is investigated for short overhead transmission lines. The proposed model incorporates a parallel branch consisting of resistance and inductance obtained through rational function fitting, which mimics the frequency-dependent behavior of the line. The coupling between multiple conductors is represented using controlled sources. Comparative analysis of fitting accuracy and computational efficiency across various orders of rational functions reveals that the first-order rational function fitting offers superior computational efficiency while maintaining high accuracy in the medium and low-frequency range. Simulation results demonstrate that the proposed model, when disregarding wave propagation effects, exhibits comparable accuracy to the distributed parameter line model while achieving higher computational efficiency. Moreover, in transient analysis predominantly influenced by power frequency, the proposed model outperforms the frequency-independent pi(π) line model in terms of accuracy.